Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the Ocean Drilling Program, 144 Scientific Results 1995
DOI: 10.2973/odp.proc.sr.144.019.1995
|View full text |Cite
|
Sign up to set email alerts
|

Physiography and Architecture of Marshall Islands Guyots Drilled during Leg 144: Geophysical Constraints on Platform Development

Abstract: Drilling during Ocean Drilling Program Leg 144 provided much needed stratigraphic control on guyots in the Marshall Islands. Information from geophysical surveys conducted before drilling and the ages and lithologies assigned to the sediments sampled during Leg 144 make it possible to compare the submerged platforms of Limalok, Lo-En, and Wodejebato with each other and with various islands and atolls in the Hawaiian and French Polynesian chains. The gross physiography and stratigraphy of the platforms drilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Calculated Te values of the study area are unusually low when comparing to other Te values in the cooling plate model (Watts et al 1980). Many researchers suggested that the lithosphere of the northwestern Pacific shows unusually thin elastic thickness <15 km (Smith et al 1989; Smith 1990; Wolfe & McNutt 1991; Bergersen 1995). Smith et al (1989) suggested the possibility of thermal rejuvenation of the lithosphere rather than the possibility of on‐ridge volcanism.…”
Section: Discussionmentioning
confidence: 99%
“…Calculated Te values of the study area are unusually low when comparing to other Te values in the cooling plate model (Watts et al 1980). Many researchers suggested that the lithosphere of the northwestern Pacific shows unusually thin elastic thickness <15 km (Smith et al 1989; Smith 1990; Wolfe & McNutt 1991; Bergersen 1995). Smith et al (1989) suggested the possibility of thermal rejuvenation of the lithosphere rather than the possibility of on‐ridge volcanism.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 94 (out of 99) atolls display polygonal shapes with large concave 'bites' (suggesting landslide scars) and linear margins (fault scars). Subsequent studies of Pacifc atolls and guyots using side-scan sonar indicate that linear margins appear to mark the head walls of ancient landslides (SMOOT, 1986;KEATING et al, 1991;KEATING, 1994a;BERGERSEN, 1995;SMOOT and KING, 1993). The side-scan sonar images of the margins of volcanic edifices show that many cusps in the coastline mark scars of ancient landslides.…”
Section: Discussionmentioning
confidence: 99%
“…Both the physical properties of the carbonate cap and the unstable nature of the volcanic foundations may be contributing factors in the failure process. Side-scan sonar images of guyots and atolls in the Pacific often show extensive turbidites draping the flanks of the seamount, and originating below the carbonate cap (e.g., BERGERSEN, 1995). Based upon observations of this nature, it appears likely that the carbonates of many atolls may be undermined by large-scale submarine landslides in the mechanical weak rock of the upper portions of the volcanic edifice, often called the transition zone.…”
Section: Discussionmentioning
confidence: 99%
“…These data were compared with the seismic profile and Ocean Drilling Project (ODP) data (Bergersen, 1995;Janet and Isabella, 1995;Abrams et al, 1992). The revealed sub-bottom structure can be divided into two layers, layer I and layer II from upper to lower (Fig.…”
Section: Sub-bottom Structure Of Seamount and Distribution Of Crustsmentioning
confidence: 99%